A Novel Conformal Quasi-Yagi Antenna With Offset Feed for High Directional 300GHz Applications - Anveshkumar Nella; Vigneswaran Dhasarathan; Jan Kriz; Tathababu Addepalli; Stepan Hubalovsky; Manish Sharma (IEEE Access, 2023)
This communication reports a conformal offset feed Quasi-Yagi antenna at 300 GHz for high-directional applications. A novel offset feed mechanism is adopted to obtain directional behavior from a conventional planar structure. The proposed antenna is designed on a Silicon-dioxide (SiO2) dielectric substrate having a permittivity ( $ε _{r}$ ) of 4 and a height of $60μ \text{m}$ . A gold material of thickness $5μ \text{m}$ is used as a conducting metal in the top and bottom layers. This antenna consists of an offset feed patch, partial ground as a reflector, and three director elements forming a Quasi-Yagi antenna. This conformal structure operates from 270 GHz to 333 GHz and provides a peak gain of 8.62dBi at 300 GHz in the end-fire direction. An analysis of different metals and parametric variation in metal thickness, substrate thickness, patch length, and width is also reported for a better understanding of the evolution of the proposed structure. A lumped equivalent circuit is also developed for the proposed structure to study its transmission line model. A good agreement is also noted between the EM simulation (HFSS, CST) and circuit simulation (ADS).